Stem Cells in the Respiratory System - Rojas, Mauricio. (Stem Cell Biology and Regenerative Medicine, 2010)
In this state-of-the-art exploration of a hugely dynamic and fast-evolving field of research, leading researchers share their collective wisdom on the role that stem cells could play in the context of physiological stress and lung injury. The text focuses on reviewing the most relevantand recentideas on using local, endogenous, and exogenous progenitor/stem cells in preventing and treating injury to the lung. The lungs are one of the most complex organs in the human body, with a mature adult lung boasting at least 40 morphologically differentiated cell lineages. Our entire blood supply passes through the lungs alveolar units during oxygenation. This interaction with the outside world, along with the intricacies of its structure, makes the lung a highly susceptible organ that is vulnerable to numerous types of injury and infection. This means that the mechanisms of lung repair are in themselves correspondingly complex. Because of their multipotentiality, as well as the fact of the lungs relatively rapid cell turnover, stem cells are thought to be an important alternative cell-base therapy in lung injury. Despite the controversial nature of stem cell research, there has been growing interest in both local and endogenous stem cells in the lung. This highly topical book with chapters on everything from using mesenchymal stem cells in lung repair to the effect of physical activity on the mobilization of stem and progenitor cells, represents an exciting body of work by outstanding investigators and will be required reading for those with an interest in the subject.